A report of the automated radiosynthesis of the tau positron emission tomography radiopharmaceutical, [18F]‐THK‐5351. (25th January 2017) - Neelamegam, Ramesh; Yokell, Daniel L.; Rice, Peter A.; Furumoto, Shozo; Kudo, Yukitsuka; Okamura, Nobuyuki; El Fakhri, Georges
Abstract : The radiotracer, [ 18 F]‐THK‐5351, is a highly selective and high‐binding affinity PET imaging agent for aggregates of hyper‐phosphorylated tau protein. Our report is a simplified 1‐pot, 2‐step radiosynthesis of [ 18 F]‐THK‐5351. This report is broadly applicable for routine clinical production and multi‐center trials on account of favorable half‐life of flourine‐18 and the use of a commercially available radiosynthesis module, the GE TRACERlab™ FXFN . First, the O‐THP protected tosyl precursor underwent nucleophilic fluorinating reaction with potassium cryptand fluoride ([ 18 F] fluoride (K[ 18 F]/K222 )) in Dimethyl sulfoxide at 110°C for 10 minutes followed by O‐THP removal by using diluted hydrochloric acid (HCl) at same temperature. [ 18 F]‐THK‐5351 was purified via semi‐preparative high‐performance liquid chromatography and formulated by using 10% EtOH, United States Pharmacopeia (USP) in 0.9% sodium chloride for injection, USP and an uncorrected radiochemical yield of 21 ± 3.5%, with a specific activity of 153.11 ± 25.9 GBq/μmol (4138 ± 700 mCi/μmol) at the end of synthesis (63 minutes; n = 3). Abstract : This work presents the cGMP radiopharmaceutical validation of the tau positron emission tomography (PET) radiopharmaceutical [ 18 F]‐THK‐5351 on the GE Tracerlab FX‐FN. We reported an uncorrected radiochemical yield of 21 ± 3.5%, with a pecific activity of 153.11 ± 25.9 GBq/μmol (4138 ± 700 mCi/μmol) at the end of synthesis (63 min; n = 3).